PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PT. AUTOKORINDO PRATAMA - Ibrahim, Rico Maulana; Cahyadi, Nur (Universitas Sarjanawiyata Tamansiswa, 2024)
This kind of research is known as causal research, which aims to determine the connection between an occurrence or the problem under study and the impact of the factors under investigation. Finding out how work discipline affects employee performance and work satisfaction as a mediating variable is the goal of this study. A quantitative approach is the research methodology employed. This study included both primary and secondary data sources. Primary data was gathered by sending questionnaires to workers, while secondary data was gathered from books, documents, and other material. With a sample of 137 Department of Production employees, the population of this study included 162 employees of PT. Autokorindo Pratama. Research employing structural equation modeling, or structural equation modeling (SEM), is the main emphasis of the data assessment method. The research results show that work discipline has a positive and significant effect on the performance of PT. Autokorindo Pratama employees, which shows that the more work discipline is applied, the better the employee's performance. Work discipline also has a positive and significant effect on job satisfaction of PT. Autokorindo Pratama employees, which shows that the more work discipline applied, the higher employee job satisfaction. PT. Autokorindo Pratama. Employee performance is not influenced by their job satisfaction. Job satisfaction cannot mediate the relationship between work discipline and employee performance.